Demographic factors as mediators between socio-psychological variables and psychological well-being in parents of children with Down syndrome - Putra, Bima Maulana; Badayai, Abdul Rahman Ahmad; Soedjiwo, Novena Ade Fredyarini; Suroyo, Suroyo; Zakaria, Siti Marziah (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
Parents of children with Down syndrome in Riau, Indonesia, encounter distinct psychological challenges, and the influence of demographic factors warrants further exploration. This study investigates the mediating role of demographics in the psychological well-being of 351 parents, employing a cross-sectional, quantitative design with purposive sampling. Standardized scales assessed psychological well-being, self-acceptance, stigma, and social support, which were analyzed using Bayesian methods. Lower self-acceptance significantly and directly correlated with poorer psychological well-being (β = −.1491, p = .0016), while higher parental education significantly predicted greater self-acceptance (β = .0119, p < .001), which in turn positively impacted well-being. Notably, older children were significantly associated with reduced social support (β = −.0101, p = .0010), and lower social support directly linked to reduced psychological well-being (β = −.1526, p = .0015). In theoretical terms, the study contributes by elucidating the indirect pathways through which demographic factors shape parental well-being within the Indonesian context. Practically, the findings underscore the need for culturally sensitive interventions focused on enhancing self-acceptance, providing accessible educational resources, and strengthening adaptive social support networks tailored to the evolving needs of parents of children with Down syndrome in Indonesia.